Alligator or crocodile? - Zimmerman, Adeline J. (2022)
"In Alligator or Crocodile?, beginning readers will learn to spot the differences between these scaly reptiles. Carefully leveled text relays what the animals look like and how they behave. Each page then asks readers to name which animal is shown in the photo. Answers appear upside down on the bottom of each page, making reading for learning interactive and fun. A See and Compare spread shows and labels each animal side by side, while a Quick Facts feature lists even more information about their similarities and differences. Children can learn more about alligators and crocodiles online using our safe search engine that provides relevant, age-appropriate websites. Alligator or Crocodile? also features reading tips for teachers and parents, photo labels, a picture glossary, a table of contents, and an index. Alligator or Crocodile? is part of Jump!'s Spot the Differences series"--
Includes index.
Ages 5-8
Keywords: Alligators -- Juvenile literature; Crocodiles -- Juvenile literature